2020
DOI: 10.12659/msm.920711
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Suicide Death among Kaposi’s Sarcoma Patients: A Surveillance, Epidemiology, and End Results Analysis

Abstract: Background: The suicide risk of patients with cancer is higher than the general population. Our research aimed to explore the Surveillance, Epidemiology, and End Results (SEER) database to define incidence and quest risk factors for death of suicide in patients with Kaposi's sarcoma (KS) in the United States (US). Material/Methods: We screened KS patients without human immunodeficiency virus status in the SEER database from 1980 to 2016, calculated the standardized mortality ratios of them by comparing the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…This study found that the suicide rate of patients with SCC in the US was higher than that in the general population,8 which is similar to the results of previous studies of the suicide rates of cancer patients in the USA11 21 22 and many other countries, including the UK, Italy, Estonia, Sweden and Denmark 3 23–26. Our analyses revealed that the factors associated with a high risk of suicide in SCC patients include being male, older at the diagnosis and white, and having a higher histological grade and not receiving surgery.…”
Section: Discussionsupporting
confidence: 89%
“…This study found that the suicide rate of patients with SCC in the US was higher than that in the general population,8 which is similar to the results of previous studies of the suicide rates of cancer patients in the USA11 21 22 and many other countries, including the UK, Italy, Estonia, Sweden and Denmark 3 23–26. Our analyses revealed that the factors associated with a high risk of suicide in SCC patients include being male, older at the diagnosis and white, and having a higher histological grade and not receiving surgery.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the proportion of male leukemia patients in the United States is similar to that of females (Table 1), whereas most suicided leukemia patients are males (85.9%), with a suicide rate of 39.96 per 100,000 person‐years, compared to 8.63 per 100,000 person‐years in female leukemia patients ( p < 0.001) (Table 2). In addition, male leukemia patients in the United States are more likely to commit suicide than are than female patients, with an HR of 4.41 (Table 3), which is similar to the suicide rates for male patients with other cancers 19,30 . Despite the similar prevalence rates of male and female leukemia patients, the much higher suicide rate in male leukemia patients may be related to the poor ability of males to withstand psychological pressures and their tendency for self‐directed violence 31,32 …”
Section: Discussionmentioning
confidence: 74%
“…In addition, male leukemia patients in the United States are more likely to commit suicide than are than female patients, with an HR of 4.41 (Table 3), which is similar to the suicide rates for male patients with other cancers. 19,30 Despite the similar prevalence rates of male and female leukemia patients, the much higher suicide rate in male leukemia patients may be related to the poor ability of males to withstand psychological pressures and their tendency for self-directed violence. 31,32 We found that most of the leukemia patients were older than 60 years (65.1%), and the suicide rate was higher in this age group (60-69 years vs. ≤39 years: HR = 2.60, 95% CI = 1.60-4.23, p < 0.001; 70-79 years vs. ≤39 years: HR = 2.84, 95% CI = 1.72-4.68, p < 0.001; ≥80 years vs. ≤39 years: HR = 2.94, 95% CI = 1.65-5.21, p < 0.001) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram, as a significant medical tool, could not only predict the risk of disease or survival outcomes but also help doctors screen high-risk patients and determine appropriate treatment measures (25,26). The predictive model accurately quantified the influence on each risk by integrating a large number of clinicopathological characteristics (27).…”
Section: Discussionmentioning
confidence: 99%